Contemporary nutrition - Wardlaw, Gordon M.; Smith, Anne M., 1955-; Collene, Angela (New York, NY : McGraw-Hill, 2013)
This text provides the ideal balance of reliable nutrition information and practical consumer-oriented knowledge. With a friendly writing style, the authors act as the student's personal guide to dispelling common misconceptions and to gaining a solid foundation for making informed nutrition choices. Includes information on MyPlate, Healthy People 2020 and Dietary Guidelines for Americans, 2010.
Includes index.
Keywords: Nutrition -- Textbooks